An effective temperature derived from a mechanistic thermophysiological model for sows reared in hot climates. (August 2022) - Huang, Tao; Zhang, Guoqiang; Brandt, Pia; Bjerg, Bjarne; Pedersen, Poul; Rong, Li
Abstract : Increased metabolic heat production caused by breeding for higher productivity puts sows at a high risk of suffering from heat stress. To reasonably predict the actual thermal status of sows becomes essential for efficiently mitigating heat stress. However, the existing thermal indices for pigs neither have been verified by experimental data of sows nor consider the effect of the dynamic heat balance within sow's body. This study proposed an effective temperature for sows (ETS) in hot climates based on an existing 2-node mechanistic thermophysiological model. The ETS was verified to be able to reflect the thermal status of sows with desired level of confidence by using physiological parameters measured sow experiments. The relative humidity and airspeeds impact ETS and effective temperature (ET), which was predicted by other four ET models, at different levels. The impact of ambient temperature on ET could be well reflected by both ETS and the four ET models. In addition, the ETSs predicted under dynamic conditions with/without considering heat storage were comparable in temperate climate. However, the thermal status of sows in hot climate was predicted more precisely by ETS obtained from dynamic conditions considering heat accumulation in the body of the sow. Considering heat storage in dynamic simulations, ETS derived based on metabolic heat production predicted the thermal status of sows better than ETS derived based on total heat loss. Highlights: An effective temperature for sows (ETS) reared in hot climates derived. Influences of relative humidity and airspeed on ETS investigated. Impact of dynamic heat accumulation within sow's body on ETS revealed. Dynamic ETS can better serve for the control of climatic conditions in pig houses.